Association of Sputum Neutrophil Extracellular Trap Subsets With IgA Anti–Citrullinated Protein Antibodies in Subjects at Risk for Rheumatoid Arthritis. Issue 1 (25th November 2021) - Okamoto, Yuko; Devoe, Stephanie; Seto, Nickie; Minarchick, Valerie; Wilson, Timothy; Rothfuss, Heather M.; Mohning, Michael P.; Arbet, Jaron; Kroehl, Miranda; Visser, Ashley; August, Justin; Thomas, Stacey M.; et al.
Abstract : Objective: Mechanisms leading to anti–citrullinated protein antibody (ACPA) generation in rheumatoid arthritis (RA) are hypothesized to originate in the lung. We undertook this study to understand associations between neutrophil extracellular trap (NET) formation in the lung and local ACPA generation in subjects at risk of developing RA. Methods: Induced sputum was collected from 49 subjects at risk of developing RA, 12 patients with RA, and 18 controls. Sputum neutrophils were tested for ex vivo NET formation, and sputum‐induced NET formation of control neutrophils was measured using immunofluorescence imaging. Sputum macrophages were tested for ex vivo endocytosis of apoptotic and opsonized cells. Levels of ACPA, NET remnants, and inflammatory proteins were quantified in sputum supernatant. Results: Spontaneous citrullinated histone H3 (Cit‐H3)–expressing NET formation was higher in sputum neutrophils from at‐risk subjects and RA patients compared to controls (median 12%, 22%, and 0%, respectively; P < 0.01). In at‐risk subjects, sputum IgA ACPA correlated with the percentage of neutrophils that underwent Cit‐H3+ NET formation (r = 0.49, P = 0.002) and levels of Cit‐H3+ NET remnants (r = 0.70, P < 0.001). Reduced endocytic capacity of sputum macrophages was found in at‐risk subjects and RA patients compared to controls. Using a mediation model, we found that sputum inflammatory proteins were associated with sputum IgA ACPA through a pathway mediated by Cit‐H3+ NET remnants. Sputum‐induced Cit‐H3+ NET formation also correlated with sputum levels of interleukin‐1β (IL‐1β), IL‐6, and tumor necrosis factor in at‐risk subjects, suggesting a causal relationship. Conclusion: These data support a potential mechanism for mucosal ACPA generation in subjects at risk of developing RA, whereby inflammation leads to increased citrullinated protein–expressing NETs that promote local ACPA generation.